Antiparasitic potential of methanol extract of brown alga sargassum polycystum (phaeophyceae) and its lc-ms/ms metabolite profiling - Fatin Khairah Haron; Muhammad Dawood Shah; Yoong Soon Yong; Jen, Kit Tan; Mohammad Tamrin Mohamad Lal; Balu Alagar Venmathi Maran (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In Southeast Asian nations, cultured hybrid groupers are facing serious infestation by the marine parasitic leech Zeylanicobdella arugamensis (Annelida, Hirudinea). They attach to the hybrid groupers by sucking and biting on the surface of the skin, paving the way for secondary infection upon the fish. The objective of the study is to utilize the locally available seaweed to control the infestation of parasitic leeches. The methanol extracts of the brown alga Sargassum polycystum C. Agardh, 1824 (Phaeophyceae) from Sabah were prepared and investigated for antiparasitic efficacy against Z. arugamensis through in vitro bioassay. A total of 126 adult leeches from the host hybrid groupers were obtained from the fish hatchery. The parasitic leeches were treated with the methanol extracts of S. polycystum for 180 min by preparing five different dosages at concentrations of 100, 50, 25, 12.5, and 6.25 mg/mL. The brown alga was found to have high antiparasitic efficacy, resulting in 100% leech mortality over a short period of time. It showed the highest antiparasitic efficacy (total mortality of leeches) in a short time limit of 0.96 ± 0.44 min, for 100 mg/mL of the extract. Observations on leech behavior in the positive control and the seaweed extract treatments showed vigorous swimming before mortality. LC-MS/MS analysis was used to reveal the phytochemical composition of the extract to understand the nature of the main components responsible for its antiparasitic activities. A total of 29 metabolites were identified via Q Exactive HF Orbitrap mass spectrometry, including two flavonoids (ephedrannin A and hinokiflavone), two organoarsenics (1-dimethylarsinoyl-heptadecane and cacodylic acid), four heterocyclic compounds, and two chlorophyll breakdown products. The presence of bioactive compounds could increase the mortality rate of parasitic leeches. Thus, this study concludes that the brown alga showed high efficacy in its antiparasitic activities and can be effectively applied for treatment in grouper aquaculture farms for sustainable aquaculture.